PENGARUH CAMPURAN MEDIA TANAM TERHADAP PERTUMBUHAN TANAMAN STROBERI (Fragaria vesca L.) SEBAGAI TANAMAN HIAS TAMAN VERTIKAL - Naomi Endah Pratiwi; Bistok Hasiholan Simanjuntak; Dina Banjarnahor (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2017)
Research on the effects of growing medium mixtures of strawberry’s (Fragaria vesca L.) growth as ornamental plants in vertical garden was implemented from April to July 2016 in anexperimental field in Salaran Getasan Village. The purpose of this study were to 1) investigate the effects of different organic medium mixtures containing soil and rice husk, cocopeat, on compost banana stem on strawberry’s growth and 2) determine the best mixture for strawberry’s vertical system. The study was conducted using a randomized block design (RBD) with 10 treatments and four replications. The treatments included different compositions of soil and each material with a mixture ratio of 1: 1, 1: 2 and 2: 1. Data were analyzed using analysis of variance and DMRT at 5% of error level as well as correlation test. Mixing organic medium as rice husk, cocopeat and compost banana stem with soil provided a significant influence on the number of leaves, number of Mixing organic medium as rice husk, cocopeat and compost banana stem with soil provided a significant influence on the number of leaves, number of shoot and shoot’s dry weight. The best growing medium mixture for strawberry’s growth was soil and rice husk with a ratio 2:1.